Bibliometric analysis of the literature on von Willebrand disease: Research status and trends - Aldossary, Nada Jaber; Rashid , Ahmed Mustafa; Waris, Abu; Siddique , Nadeem; Khan , Muhammad Ajmal; Javaid , Syed Sarmad; Al-Rubaish , Omar I.; Mohiuddin , Shamim Shaikh; Lasrado, Savita; Menezes, Ritesh G. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Von Willebrand disease (VWD) is considered the most prevalent inherited bleeding disorder. The current study aims to demonstrate the research status and trends on VWD worldwide. Methods: Bibliometric analysis was used to investigate the global research productivity and trends on VWD. The publications on VWD from 1956 to 2021 were extracted using the Web of Science database. In the VWD domain, a total of 3,643 records were analyzed for authorship and collaboration patterns, yearly productivity, highly cited documents, relevant source of publication, most prolific scholars, productive countries, and organizations. Results: The most productive journal, author, organization, and country were 'Haemophilia' with 439 publications, 'Favaloro EJ' with 119 publications, the 'University of Milan' with 192 publications, and the United States of America (USA) with 1,048 publications, respectively. The document with the highest citations was 'Srivastava A, 2013, Haemophilia,' which received 1,154 citations in total. In 2016, the highest number of publications shared by two author patterns was 28. With 199 publications, the year 2021 remained on the top, while the citation-wise analysis identified 2006 as the top year with 5,379 citations. Conclusions: Research productivity and publication trends on VWD revealed that the USA emerged as the most significant contributing country. The 'University of Milan' was the most significant contributing organization, while ‘Favaloro EJ’ was the most significant author. 'Hemophilia' was found to be the most significant journal in the field of VWD. It is recommended that researchers from countries with significant contributions to the field should collaborate with researchers from Asian countries and other countries that lack behind in research in the domain of VWD.(www.actabiomedica.it)